1991
DOI: 10.1017/s0021859600076139
|View full text |Cite
|
Sign up to set email alerts
|

Uptake, cycling and fate of nitrogen in grass-clover swards continuously grazed by sheep

Abstract: S U M M A R YComponents of the N cycle were studied at Hurley, UK, in 1985-87. In grass-clover {Lolium perenne and Trifolium repens) swards, grazed at three intensities, low total inputs of N were associated with low outputs and losses of N. Nevertheless, the flows (intake and excretion) of N through animals were substantial and gave rise, at the higher intensities of grazing, to an acceptably high agricultural output per hectare. This was considered evidence of a fast and efficient recycling of N between plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
1
3

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(58 citation statements)
references
References 38 publications
(52 reference statements)
4
50
1
3
Order By: Relevance
“…, similar to that observed in the UK (Parsons et al 1991;Andrews et al 2007) and NZ (Woodfield and Clark 2009), although Jarvis (1993) suggested that in the UK, dairy pastures were typically much lower in both clover content (<10%) and the amount of N 2 fixed (10 kg ha -1 year -1 ). These low clover contents are likely to be suboptimal in terms of dairy production (Woodfield and Clark 2009) as well as N 2 fixation and thus efforts to increase N 2 fixation should be rewarded with increased milk production efficiency.…”
Section: The Achilles Heel: Low White Clover Content Of Pasturessupporting
confidence: 71%
See 1 more Smart Citation
“…, similar to that observed in the UK (Parsons et al 1991;Andrews et al 2007) and NZ (Woodfield and Clark 2009), although Jarvis (1993) suggested that in the UK, dairy pastures were typically much lower in both clover content (<10%) and the amount of N 2 fixed (10 kg ha -1 year -1 ). These low clover contents are likely to be suboptimal in terms of dairy production (Woodfield and Clark 2009) as well as N 2 fixation and thus efforts to increase N 2 fixation should be rewarded with increased milk production efficiency.…”
Section: The Achilles Heel: Low White Clover Content Of Pasturessupporting
confidence: 71%
“…Generally to minimise losses of N via denitrification, leaching or NH 3 volatilisation a 'tight' N cycle is required, necessitating the maintenance of some N limited grass to 'mop up' available N (Parsons et al 1991). However, it is generally thought that a system with slightly N-deficient grass may limit feed quantity and quality and is not considered optimised in terms of animal production (Eckard 2001).…”
Section: Environmental Costs and Benefits Of N 2 Fixationmentioning
confidence: 99%
“…Isto tem levado a um aumento do interesse pelo uso de leguminosas, devido a seu baixo impacto, mas reduzindo o rendimento dos sistemas pastoris. Tais benefícios podem ser encontrados em ambos os sistemas, simplesmente pela redução, sobretudo da fertilização nitrogenada, e assim, possivelmente, da produtividade do sistema (PARSONS et al, 1991). Uma exceção é a Nova Zelândia (NZ) onde uma pastagem consorciada bem manejada, freqüentemente tem produções de forragem entre 10 -15t de MS/ha/ano (DALY, 1990).…”
Section: Introductionunclassified
“…There is a short window of time between the average harvest date of canola (15 September) and the latest date for PS fall application to land (1 October) in Québec. This means that slurry is usually applied on recently harvested crop residues, which may slow down the infiltration of slurry into the soil and lead to greater NH 3 volatilization losses than when slurry is applied on a bare soil (Parsons et al 1990). Rapid incorporation of slurry following application has been shown to reduce volatilization of ammonia .…”
mentioning
confidence: 99%